An application of the method of matched asymptotic expansions for low Reynolds number flow past a cylinder of arbitrary cross section - Mirela Kohr (International Journal of Mathematics and Mathematical Sciences)
We study the low Reynolds number flow of an incompressible Newtonian fluid of infinite expanse past a cylinder of arbitrary cross section by using the method of matched asymptotic expansions. The analysis that will be made in this paper is equivalent to that developed by Power (1990) in order to solve the resulting inner (or Stokes) problems with the completed double-layer boundary integral equation method (CDLBIEM) due to Power and Miranda (1987). We will solve these problems by the boundary integral method developed by Hsiao and Kress (1985).